Food-drug interactions: Modelling knowledge and attitude among healthcare professionals at the Ho Teaching Hospital - Donatus Wewura Adongo; David Adedia; Augustine Tandoh; Hilda Amekyeh; Killian Asampana Asosega; Charles Kwaku Benneh; Eli Yao Lawluvi; Inemesit Okon Ben; Abigail Hohoayi; Ebenezer Wiafe; Jones Ofori-Amoah; Salifu Nanga; et al. (PLoS ONE, 2025)
Background Food-drug interactions (FDIs) are a significant clinical concern, impacting the effectiveness and safety of treatments. Healthcare professionals (HCPs) play a crucial role in minimizing these risks through appropriate patient education. The Ho Teaching Hospital (HTH) in Ghana serves a large patient population with varying medication needs. However, there is limited data on the knowledge and attitudes of HCPs regarding FDIs in this setting. Aim This study assessed and modelled the knowledge and attitudes of HCPs towards FDIs at HTH. Methodology A cross-sectional survey of 300 HCPs, including medical doctors, pharmacists, nurses, midwives, and dietitians, was conducted using a self-administered questionnaire. Data were analyzed using Kruskal-Wallis tests, logistic regression models and path analysis. Results The mean knowledge score on FDIs was 27.52 (SD = 8.71) out of 61, indicating low knowledge. Pharmacists scored the highest, while profession and sex significantly influenced knowledge levels (p < 0.05). Only 39% of participants demonstrated high knowledge, and 49.70% exhibited a good attitude towards FDIs. Males were less likely to show good attitudes compared to females (aOR = 0.15; p = 0.038). HCPs who attended FDI training (aOR = 1.83; p = 0.027) and Christians (aOR = 2.17; p = 0.048) displayed more favorable attitudes. The mediation analysis revealed that knowledge of alcohol-drug interactions influences overall attitudes through pathways involving knowledge of drug-food time intervals. Conclusion Knowledge of FDIs among HCPs is inadequate, with significant variability across professions. Pharmacists demonstrated the highest knowledge levels, while overall attitudes varied by sex, training, and religious affiliation. These findings highlight the need for targeted educational programs and training for HCPs regarding FDIs.